The Role Of Streptococcus Mutants In Dental Caries In Two Groups Of Sensitive And Resistance Children Age Between 3 To 5 Years - Abbas Rahimi Forushani; Mohammad Kazem Sharifi Yazdi; Fariborz Mehrani; Hossein Dargahi; Mohammad Mehdi Soltan Dallal; Seyed Asghar Miremadi (Tehran University of Medical Sciences, 2013)
Background and Aim: Dental caries in children caused by repeatable consumption of sweet product especially at night, that itself mostly depend on economic and cultural background of the society and family.One of the most common diseases of human being is dental caries, which are caused by many factors, such as microorganisms, dieting, passing time, and the host itself. Among the microorganisms Streptococci mutants play the major role in causing dental caries. The aim of this research was to investigate the role of Streptococci mutants in dental caries between two groups of children sensitive and resistance to caries. Materials and Methods: This was a cross-sectional research, in which 120 children(60 susceptible and 60 resistance) aged between 3 to 5 referred to Tehran University dental school were selected randomly. The selection criteria for the sensitive and resistance dental caries were dmfs > 5 and dmfs < 10 respectively. None of the groups had used any drug or fluoride products before sampling. Saliva of both groups were collected, and transferred to the specific culture media(Mitis Salivarious Agar). After incubation at 37 oC colonies of S.mutans were counted. Results: There was a significant difference between the number of colony counting(cfu/ml) with age and consumption of repeated sugar product, while. there was no significant difference between(cfu/ml) sex, oral hygiene, and nutrition period during infancy. Conclusion: The results of this study showed that the consumption of sugar product in childhood results in dental carries.